86.5k views
2 votes
Find the derivative of 1/(2x-1)^2

User Jreikes
by
5.3k points

1 Answer

3 votes

Answer:


\displaystyle (dy)/(dx) = (-4)/((2x - 1)^3)

General Formulas and Concepts:

Calculus

Differentiation

  • Derivatives
  • Derivative Notation

Derivative Property [Multiplied Constant]:
\displaystyle (d)/(dx) [cf(x)] = c \cdot f'(x)

Derivative Property [Addition/Subtraction]:
\displaystyle (d)/(dx)[f(x) + g(x)] = (d)/(dx)[f(x)] + (d)/(dx)[g(x)]

Basic Power Rule:

  1. f(x) = cxⁿ
  2. f’(x) = c·nxⁿ⁻¹

Derivative Rule [Chain Rule]:
\displaystyle (d)/(dx)[f(g(x))] =f'(g(x)) \cdot g'(x)

Explanation:

Step 1: Define

Identify


\displaystyle y = (1)/((2x - 1)^2)

Step 2: Differentiate

  1. Rewrite:
    \displaystyle y = (2x - 1)^(-2)
  2. Basic Power Rule [Derivative Rule - Chain Rule]:
    \displaystyle y' = -2(2x - 1)^(-3)(2x - 1)'
  3. Basic Power Rule [Derivative Properties]:
    \displaystyle y' = -4(2x - 1)^(-3)
  4. Rewrite:
    \displaystyle y' = (-4)/((2x - 1)^3)

Topic: AP Calculus AB/BC (Calculus I/I + II)

Unit: Differentiation

User JuFo
by
5.2k points